Experimental and numerical study on transient heat transfer for helium gas flowing over a flat plate containing an exponentially increasing heat source - Zhou ZHAO (The Japan Society of Mechanical Engineers, 2014)
This study is aimed to obtain fundamental data of transient heat transfer and clarify transient heat transfer process between the surface of solid and the neighboring helium gas in Very High Temperature Reactor (VHTR). Such studies are important for both of the academic knowledge on the complex transient phenomena and the safety assessment of severe nuclear reactor accidents such as power burst, rapid depressurization and withdraw of control rods. In this paper, a series of flat plates with different widths under different pressures inside a circular channel have been experimental tested and numerical analyzed for forced convection transient heat transfer for helium gas flowing over the plate. The heat generation rate of the plate was increased with a function of Q0exp(t/τ) (where t is time and τ is period of heat generation rate or e-fold time). The plates were made of platinum with a thickness of 0.1 mm and widths of 2 mm, 4 mm and 6 mm. Based on the experimental data and our previous research (Liu, et al. 2008a), we found that when the period τ is longer than around 1 second the heat transfer coefficients approach the quasi-steady-state values but when the period is shorter than around 1 second the heat transfer coefficients become higher as the period decreases. In this paper, we found that the conductive heat transfer becomes predominant for the period less than around 1 second and the heat transfer is mainly governed by convection heat transfer in the quasi-steady-state for the period larger than around 1 s. A semi-empirical correlation of surface temperature difference for plate heater was obtained based on the experimental data and analytic results. A 3-dimensional numerical simulation was carried out for the purpose of obtaining the plate temperature changes with time at various periods and velocities. The numerical solutions agree well with the experimental data within 6% differences.